Anti-infective peptide LL37 sustained delivery system — a potential novel treatment method of ocular infections. Report 2. Antiviral properties of silica nanoparticle encapsulated LL37 (Ukrainian Journal of Ophthalmology, 2026)
Purpose. To test anti-viral activity of anti-infective peptide (AIP) LL37 sustained release system (SRS) based on silica nanoparticles.Material and Methods. AIP LL37 (cathelicidin) was encapsulated in silica nanoparticles (SiNP) under magnetic stirring. For antiviral activity testing, human corneal epithelial cell (HCEC) culture was infected by type I herpes simplex virus (HSV). SiNP encapsulated LL37 or empty SiNP or free LL37 were added to the infected HCEC after that and were co-cultured for additional 24—72 h. Culture medium was collected to count virus titer using plaque formation assay.Results. SiNP encapsulated LL37 had significant antiviral effect against HSV compared to control: virus titer in culture medium contained SiNP encapsulat¬ed LL37 was 91,2+49,7plaque forming units (PFU) per ml. in 24 h culturing and 44333,3+8891,9 PFU/ml in 72 h culturing. At the same time, virus titer in culture medium without SRS of AIP LL37 was 6716,7+3489,6 PFU/ml and 327500+36159,4PFU/ml in 24 h and 72 h culturing respectively (P = 0,024).Conclusion. For the first time it was shown in vitro activity of anti-infective peptide LL37sustained release system based on silica nanoparticles against the common-drug delivery, est ocular viral infection — herpes simplex virus.
Keywords: eye infection; LL37; Antagonists peptide system 0f constant delivery; herpes simplex virus